Optimization of carbon gain in canopies of Mediterranean evergreen oaks - Rambal, S.; Damesin, C.; JOFFRE, R.; Méthy, M.; Lo Seen, D. (Ann. For. Sci., 1996)
The main goal of this study was to analyze the depth-distribution of leaf mass per area (LMA) measured in ten canopies of Mediterranean evergreen oaks, five canopies of Quercus coccifera and five canopies of Q ilex, across soil water availability gradients in southern France, Spain and Portugal. There was a significant site effect on LMA with values being lower in mesic sites compared to those on xeric sites. In all canopies, LMA decreased by up to 50% from the top to the bottom. The relationships between cumulative leaf area index and LMA could be represented by an exponential function. For two canopies of Q ilex growing in contrasting environments, we analyzed the interrelationships among LMA, mass-based nitrogen, mass-based metabolic versus structural (total fiber) content, photosynthetic electron transport and carbon isotope composition. There was no difference in mass-based nitrogen or fiber content among upper and lower canopy positions in both locations. The maximum quantum yield of linear electron flow can be considered to be constant within the canopy. The area-based maximal electron transport rate and the carbon isotope composition were significantly linearly related to the LMA. Finally, we tested whether the observed depth-distribution follows the pattern suggested by some optimization theories.
Keywords: Leaf mass per area; Mediterranean evergreen canopy; photosynthesis-related leaf property; Quercus coccifera; Quercus ilex